Ticagrelor monotherapy versus aspirin in patients undergoing multiple arterial or single arterial coronary artery bypass grafting: insights from the TiCAB trial. (21st November 2019) - Sandner, Sigrid E; Schunkert, Heribert; Kastrati, Adnan; Wiedemann, Dominik; Misfeld, Martin; Böning, Andreas; Tebbe, Ulrich; Nowak, Bernd; Stritzke, Jan; Laufer, Günther; von Scheidt, Moritz; ,
Abstract: : OBJECTIVES: We evaluated the effect of ticagrelor monotherapy on outcomes after multiple arterial grafting (MAG) or single arterial grafting (SAG) in coronary artery bypass grafting (CABG). METHODS: In a post hoc, non-randomized analysis of the TiCAB (Ticagrelor in CABG; ClinicalTrials.gov NCT01755520) trial, we compared event rates for ticagrelor versus aspirin in patients undergoing MAG and SAG. Primary outcome was the composite of cardiovascular death, non-fatal myocardial infarction (MI), stroke or repeat revascularization 1 year after CABG. Secondary outcomes included individual components of the primary end point, all-cause death and bleeding. RESULTS: Among 1753 patients, 998 patients underwent MAG and 755 patients underwent SAG. There was no significant difference in the 1-year primary composite outcome for ticagrelor versus aspirin with MAG [7.2% vs 7.9%; hazard ratio (HR) 0.90, 95% confidence interval (CI) 0.57–1.43; P  = 0.66] or SAG (12.3% vs 8.6%; HR 1.47, 95% CI 0.93–2.31; P  = 0.10). Event rates for cardiovascular death, MI, stroke, repeat revascularization and all-cause death were similar for both treatment groups with MAG and SAG. No significant difference in major bleeding was observed for ticagrelor versus aspirin with MAG (2.6% vs 2.7%; HR 0.95, 95% CI 0.44–2.05; P  = 0.90) or SAG (5.8% vs 4.0%; HR 1.49, 95% CI 0.77–2.89; P  = 0.24). CONCLUSIONS: In patients undergoing either MAG or SAG in the TiCAB trial, ticagrelor monotherapy compared with aspirin did not affect the rate of cardiovascular death, non-fatal MI, stroke or repeat revascularization, or the rate of bleeding, at 1 year after CABG.